A PEACE COMMUNICATION AS LEARNING PROCESS: A SOCIO-RELIGIOUS CONFLICT RESOLUTION MODEL IN LOMBOK - Hidayatul Ummah, Athik; Abdullah Acim, Subhan (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This article explores socio-religious conflict resolution in Lombok through the lens of peace communication as a learning process embedded in power relations and cultural practices. While the state formally addressed conflict through mediation and interfaith dialogue under the discourse of harmony, mechanisms for preventive protection and trauma-sensitive recovery for minority groups remained insufficient. Consequently, conflict resolution practices tended to privilege social order and majoritarian norms over the substantive realization of freedom of religion or belief. Employing a qualitative case study approach, this research draws on in-depth interviews, participant observation, and documentation involving religious leaders, community actors, and conflict-affected minorities. The findings reveal that state-led dialogue largely reproduces a depoliticized notion of peace, where harmony is defined as the absence of visible tension rather than as a process of justice, recognition, and equality. In contrast, the Mareje community developed a grassroots model of peace communication grounded in local wisdom, particularly gawe rapah, which operates as a counter-hegemonic learning space. Through collective rituals, shared memory, and everyday interaction, this model enables the reconstruction of trust, the negotiation of difference, and the intergenerational transmission of coexistence values. This study argues that socio-religious conflict resolution in Lombok should be understood as a form of critical peace education, where learning functions not only to restore social relations but also to challenge dominant frameworks of harmony. By situating peace communication within local cultural praxis, this research contributes to critical peace studies and debates on inclusive and transformative conflict resolution.